Pengaruh Tarif Pengenaan Pajak Penghasilan Pasal 21 Terhadap Keputusan Klaim Jaminan Hari Tua Sebagian Di BPJS Ketenagakerjaan Jakarta Kelapa Gading - Mega Nur Octavia; Ajat Sudrajat (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to analyze the effect of the imposition of Article 21 Income Tax on the Decision to Claim Partial Old Age Security at BPJS Ketenagakerjaan Jakarta Kelapa Gading. The analysis was carried out on BPJS Ketenagakerjaan Jakarta Kelapa Gading with the research subjects of the JHT-JP Jakarta Kelapa Gading Intermediary Service and participants using Partial Old Age Insurance. Then the research method used is descriptive qualitative analysis with interview and observation instruments. The results of the study show that there is no perfect policy, there must always be shortcomings in a policy because every community has different views, problems, interests and needs. However, in relation to this JHT program, BPJS Employment provides a solution by preferring the program to increase benefits.